Investigating the Relationship between Transformational Leadership, Compensation, and Teacher Performance through Organizational Commitment in an Islamic Foundation Setting - Soelistya, Djoko (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study delves into the Islamic Foundation for Education Malik Ibrahim Gresik to investigate how transformational leadership and compensation, mediated through organizational commitment, impact teacher performance. Employing a quantitative explanatory approach, the analysis reveals several key insights. Firstly, teacher performance is directly affected by transformational leadership and compensation. Secondly, both transformational leadership and compensation directly influence organizational commitment. Thirdly, organizational commitment directly impacts teacher performance. Transformational leadership independently impacts teacher performance, circumventing the need for organizational commitment as a mediator. Additionally, organizational commitment serves as a mediator between compensation and teacher effectiveness. These findings hold significant implications for educational management. They underscore the importance of prioritizing transformational leadership and fair compensation to enhance educational effectiveness. Moreover, they highlight the need for fostering organizational commitment among educators. By addressing these factors, educational institutions can bolster their management practices, thereby elevating the quality of education and contributing more substantially to the nation's development agenda.